Physicochemical Analysis of Honey Produced and Sold in the Municipality of Senhor do Bonfim, Bahia - Silva , Willhams Andrade; Moura , Claudete Maria da Silva; Araújo , Alessandra Oliveira de; Santos , Laianne Oliveira; Silva , Rafael Abílio de Sousa; Ribeiro , Paulo Leonardo Lima; Gois, Glayciane Costa (Acta Scientiarum. Animal Sciences, 2025)
The objective of this study was to analyze the physicochemical characteristics of Apis mellifera L. honey produced and sold in Senhor do Bonfim, Bahia, Brazil. A completely randomized design was adopted; it consisted of 6 treatments and 4 replicates, with the honey collection sites being considered as the treatments, namely: T1CMQ - Quicé Honey House, T2AMt - Maranata Apiary, T3FLv - Senhor do Bonfim Street Market, T4AMT - Monte Tabor Apiary, T5AJVC - Juvêncio Apiary and T6AS - Souza Apiary. The honeys in the different treatments analyzed showed similarity for moisture, total titratable acidity and Lund reaction (p > 0.05). The lowest ash and total soluble solids contents were obtained by the T3FLv honey samples (p < 0.05). The highest pH was obtained in the T1CMQ samples (p < 0.05). The honeys were classified as having a color between extra light amber and light amber. The Lugol test was negative. The results found show that the honey produced and sold in Senhor do Bonfim, BA, is of good quality and suitable for human consumption.